Contesting Science That Silences: Amplifying Equity, Agency, and Design Research in Literacy Teacher Preparation. (3rd September 2020) - Hoffman, James V.; Hikida, Michiko; Sailors, Misty
ABSTRACT: In this article, we argue that the "science of reading" (SOR) construct is being used to shape the future of literacy teacher preparation and silence the voices and work of literacy teacher education researchers to the detriment of quality science, quality teaching, and quality teacher preparation. First, we briefly inspect the SOR movement in terms of its historical roots in experimental psychology. Next, we examine the claims being made by SOR advocates regarding the absence of attention to the SOR literature in teacher preparation programs, and the related claims for the negative consequences that occur when these so‐called underprepared teachers enter the workforce. Then, we present literature reviews, drawn from a large and dynamic database of research on literacy teacher preparation (over 600 empirical studies that were published between 1999 and 2018); the studies in the database have been excluded from the SOR. Finally, we conclude with a discussion of equity, agency, and design as a pathway forward in improving literacy teacher preparation.